Directional Echo Sounding on Hydrographic Surveys - Cohen, Philip M. (The International Hydrographic Review, 2018)
Results obtained by using directional sounding equipment are presented together with a discussion and illustrations. It is shown that directional traces can be considered slope-corrected and that they exhibit other characteristics which can be utilized to advantage on hydrographic surveys in deep ocean areas.